Moments that matter: childhood pain treatment shapes pain for life—we can do better every time in every child - Rebeccah Slater; Suellen Walker; Christopher Eccleston; Carlo Bellieni; Tanvi Hirekodi; Ricardo Carbajal; Lucinda Smart; William Laughey; Maria M. Cobo; Stefan Friedrichsdorf (BMC Medicine)
Abstract Background Needle procedures, such as vaccinations, blood draws, and intravenous cannulation, are the most frequent source of childhood pain, causing fear and reducing the uptake of medical procedures. Every child has the right to expect pain relief, and we have evidence-based tools to reduce needle procedure-related pain. Therefore, the lack of analgesic provision for needle pain is not justified. We argue that better informed and motivated healthcare professionals and families can advocate for appropriate pain relief in every child, every time. Observations Engaging communication campaigns are needed to educate our healthcare professionals. Evidence-based modalities such as topical anaesthesia, sucrose or breastfeeding, comfort positioning, and age-appropriate distractions should be available for every child during needle procedures. However, high-quality information is not enough to change behaviour—healthcare professionals need to be motivated, encouraged, and inspired. Parents and carers should be empowered to advocate for their children and be aware that their child has the right to receive pain relief during these procedures. Conclusions and relevance This is a call to action—we need collaboration between academics, healthcare professionals, industry and charities, to expedite behavioural change and parental advocacy through high-quality communication strategies. Effective pain management in infants and children can play a crucial role in promoting the uptake of vaccinations and medical procedures and can influence future attitudes to pain.